Digital Da’wah and Visual Pedagogy: An Empirical Study of Infographic Based Islamic Religious Education among UMS Student (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
The rapid development of digital media has transformed Islamic da’wah practices in higher education, particularly among university students who are closely engaged with the visual culture of social media. This study examines infographic content design as a medium of digital da’wah for Islamic Religious Education (IRE) among students at Universitas Muhammadiyah Surakarta (UMS) using a qualitative phenomenological approach. Data were collected through in-depth interviews, digital observations, and documentation of Instagram content involving UMS students as active users. The findings indicate that infographics function effectively as both pedagogical and persuasive media by translating abstract Islamic values into concise, well-structured visual messages that align with students’ digital consumption patterns. Visual clarity, aesthetic coherence, and narrative simplicity emerged as key design elements that enhance students’ understanding, engagement, and reflective awareness, while repeated exposure to infographic content contributes to the gradual internalization of religious values. The novelty of this study lies in integrating visual communication principles and the Cognitive Theory of Multimedia Learning within the context of Islamic digital da’wah in a faith-based university, highlighting infographic design as a mediating mechanism between pedagogical objectives and the contemporary visual culture of Muslim university students.